Brazil : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2018)
Brazil is the largest country in Latin America with a varied geography and a population of over 200 million spread across 26 diverse states, generating wide-ranging infrastructure needs. Over the decades, many government investment initiatives have been launched to address these needs, however there remains a significant infrastructure gap in Brazil which continues to hamper growth potential. Over the past two decades, public investment has been considerably below the regional and income group averages and this has translated into much lower capital stock. Public investment averaged around 2 percent of GDP during the period 1995 to 2015, compared with 6.4 percent for Emerging Market Economies (EME) and 5.5 percent for Latin American Countries (LAC). As a result, public capital stock in 2015 was only 35 percent of GDP compared with an average of 92 for EME and 87 for LAC.